Ecological principles of colonisation resistance in the gut microbiome - Spragge, F (2023)
The mammalian gut is home to hundreds of species of microbes, collectively known as the gut microbiome. A key benefit conferred by the gut microbiome is protection against pathogens, known as colonisation resistance. The importance of colonisation resistance by the microbiome has been recognised for decades. A range of potential mechanisms underlying the protection against pathogens have been identified, including direct competition between the resident microbiota and pathogens. But when I started my research for this thesis, understanding how they work was restricted to specific communities and contexts and we lacked the ability to understand why one microbial community is protective while another is not. In this thesis I take an ecological approach to the human microbiota to seek general rules of colonisation resistance and discover two key ecological principles and the mechanism that underlies them.